2010
DOI: 10.1590/s1415-43662010000600014
|View full text |Cite
|
Sign up to set email alerts
|

Alternativas para a agregação de valor aos resíduos da industrialização de peixe

Abstract: RESUMOO setor pesqueiro, em especial a pesca extrativa marinha, é uma atividade de grande importância econômica em diversas localidades do Brasil. A industrialização de peixe gera uma quantidade expressiva de resíduos ricos em proteínas e em ácidos graxos de cadeia longa, entre os quais se destacam os insaturados da série ômega-3. Este trabalho teve como objetivo fazer uma revisão sobre as alternativas tecnológicas disponíveis para aproveitamento de resíduos de peixe, como maneira de se agregar valor a este ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
32

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 48 publications
0
28
0
32
Order By: Relevance
“…The same research group reported the alkali-catalyzed methanolysis of biodiesel from beef tallow in a pilot plant (Cunha et al, 2009 (FAO, 2010). This oil could be applied as substrate for the production of biodiesel (Feltes et al, 2010). In 2009, the total fisheries production in Brazil was more than 1.24 million tonnes.…”
Section: Animal Fats and Oilsmentioning
confidence: 99%
“…The same research group reported the alkali-catalyzed methanolysis of biodiesel from beef tallow in a pilot plant (Cunha et al, 2009 (FAO, 2010). This oil could be applied as substrate for the production of biodiesel (Feltes et al, 2010). In 2009, the total fisheries production in Brazil was more than 1.24 million tonnes.…”
Section: Animal Fats and Oilsmentioning
confidence: 99%
“…Verifica-se aumento no teor de aminoácidos livres, peptídeos de cadeia curta e nitrogênio não proteico com a redução no nível de proteína bruta (Feltes et al, 2010).…”
Section: Introductionunclassified
“…In general, marine fish, shrimp and mollusc oils are rich dietary sources of the n-3 series of essential fatty acids (EFA); oils whose eicosapentaenoic acid (20:5 n-3; EPA) and docosahexaenoic acid (22:6 n-3; DHA) content constitutes over 20% of the total fatty acids include cod liver oil, cuttlefish liver oil, shortnecked clam oil, sardine oil, skipjack oil, shrimp head oil and squid liver oil (Chamberlain, 1993;Bandarra et al, 2006;Feltes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%